2007
DOI: 10.1002/jcb.21100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the magnolol‐induced cell death of CGTH W‐2 thyroid carcinoma cells

Abstract: Magnolol, a substance purified from the bark of Magnolia officialis, inhibits cell proliferation and induces apoptosis in a variety of cancer cells. The aim of this study was to study the effects of magnolol on CGTH W-2 thyroid carcinoma cells. After 24 h treatment with 80 microM magnolol in serum-containing medium, about 50% of the cells exhibited apoptotic features and 20% necrotic features. Cytochrome-c staining was diffused in the cytoplasm of the apoptotic cells, but restricted to the mitochondria in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 44 publications
5
26
0
Order By: Relevance
“…Magnolol triggers the release of Bid, Bax and cytochrome c from mitochondria, and induces apoptosis via a caspase-independent pathway in non-small cell lung cancer cells [7]. Induction of apoptosis by magnolol has been reported to mediate through caspaseindependent pathway and G2/M phase arrest in human breast cancer cells [9], and through cytochrome c/caspase 3/PARP and PTEN/Akt pathways in thyroid carcinoma cells [28]. The regulatory pathways of MM1-induced apoptosis in different cancers, on the other hand, are poorly understood at present.…”
Section: Discussionmentioning
confidence: 99%
“…Magnolol triggers the release of Bid, Bax and cytochrome c from mitochondria, and induces apoptosis via a caspase-independent pathway in non-small cell lung cancer cells [7]. Induction of apoptosis by magnolol has been reported to mediate through caspaseindependent pathway and G2/M phase arrest in human breast cancer cells [9], and through cytochrome c/caspase 3/PARP and PTEN/Akt pathways in thyroid carcinoma cells [28]. The regulatory pathways of MM1-induced apoptosis in different cancers, on the other hand, are poorly understood at present.…”
Section: Discussionmentioning
confidence: 99%
“…Their efficacy is higher, and side effects are significantly lower than with synthetic compounds (Baker et al 2007). Obovatol (5-prop-2-enyl-3-(4-prop-2-enylphenoxy)benzene-1,2-diol) (OBO), a newly found compound isolated from extracts of Magnolia obovata, is supposed to have great therapeutic potential as suggested by antitumor, anti-depressant, and antiinflammatory activity (Huang et al 2007;Xu et al 2008;Choi et al 2007;Lee et al 2008a). However, the mechanism underlying its biological action is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of studies have drawn attention to the anticancer properties of magnolol. Previous studies have revealed that magnolol inhibits the proliferation and induces the apoptosis of several cancer cell lines including colon cancer, HepG2 hepatoma, leukemia, fibrosarcoma, melanoma, squamous carcinoma, and thyroid carcinoma cells (Lin et al, 2001(Lin et al, , 2002Yang et al, 2003;Zhong et al, 2003;Huang et al, 2007). However, the potential anticancer properties of magnolol against NSCLC are not well-known.…”
Section: Introductionmentioning
confidence: 95%